IMPLEMENTASI TUGAS PENGHULU TERKAIT PEMBANGUNAN JALAN PEDESAAN BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 84 TAHUN 2015 TENTANG SUSUNAN ORGANISASI DAN TATA KERJA PEMERINTAHAN DESA DI KAMPUNG DAYUN KECAMATAN DAYUN KABUPATEN SIAK PROVINSI RIAU - Syahputra, Julpan; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The implementation of road construction is the most basic means that aim to support the smooth running of human transportation networks. The welfare of the community can be seen from the physical condition of the area regarding the facilities provided by the government. Building village independence within the village framework must begin with a good village planning process, and be followed by good program governance as well. Effective rural development is not merely an opportunity but the result of determining priority choices for good planning activities. The village government as the lowest government unit plays a frontline role in governance and development. In the Regulation of the Minister of Home Affairs Number 84 of 2015 concerning the Organizational Structure and Work Procedure of Village Administration, Article 6 paragraph (2) states that